In vitro fracture resistance of endodontically treated premolar teeth restored with a direct layered fiber-reinforced composite post and core - Forster András; Sáry Tekla; Braunitzer Gábor; Fráter Márk Tibor (2017)
Methods for restoring endodontically treated teeth fall short of restoring the physiologic mechanical properties. Fracture of endodontically treated teeth is a common type of clinical failure. New treatment modalities or perfected versions of existing treatment concepts need to be tested to find a biomimetic solution. A novel method of restoring endodontically treated teeth is presented and compared in vitro with currently accepted restorative methods. Seventy-two extracted and endodontically treated maxillary premolar teeth were divided into six groups (n = 12) depending on restorative technique (Groups 1–6). Group 1: fiber-reinforced composite post (FRC), Group 2: direct layered short FRC post and core, Group 3: short fiber-reinforced obliquely layered composite restoration, Group 4: microhybrid composite restoration, Group 5: fiber-reinforced box, Group 6: control. Specimens were submitted to static fracture resistance test. Fracture thresholds and fracture patterns were evaluated. Group 6 exhibited the highest fracture resistance. Group 2 yielded the highest fracture resistance among the restored groups. The fracture resistance of Group 2 did not differ significantly from Group 6. Groups 1, 3, 4, 5 proved to be significantly different from the control group. There was no statistically significant difference among restored groups. Fracture patterns of tested groups were dominantly non repairable opposed to control groups mostly repairable fractures. Application of direct-layered short FRC post and core in endodontically treated premolars performed statistically similarly in the studied conditions as natural teeth. Therefore, it seems a promising alternative to current endo-restorative solutions. However, further testing is required. © 2016 Informa UK Limited, trading as Taylor & Francis Group